Pengaruh Kualitas Pelayanan dan Brand Image Terhadap Loyalitas Pelanggan Pada Kopi Kenangan Di Mustikajaya - Afrilianna Anastasia Rotua Silitonga; Trie Andari Widyastuti (JAMBIS : Jurnal Administrasi Bisnis, 2025)
Abstract.This study aims to analyze the influence of service quality and brand image on customer loyalty at KopiKenangan in Mustikajaya. The research is motivated by the intense competition in the ready-to-drink coffeeindustry, which requires companies to maintain excellent service quality and a strong brand image to sustaincustomer loyalty. This study employs a quantitative approach using a survey method by distributingquestionnaires to 60 customers of Kopi Kenangan in Mustikajaya. Data were analyzed using validity andreliability tests, classical assumption tests, and multiple linear regression analysis. The results indicate thatservice quality has a positive and significant effect on customer loyalty (β = 0.421; t = 4.112; sig = 0.000).Brand image also shows a positive and significant effect on customer loyalty (β = 0.389; t = 3.884; sig =0.000). Simultaneously, service quality and brand image significantly influence customer loyalty (F = 42.118;sig = 0.000). The coefficient of determination (R²) value of 0.623 indicates that 62.3% of customer loyaltyvariation is explained by service quality and brand image, while the remaining 37.7% is influenced by otherfactors outside this study. These findings confirm that improving service quality and strengthening brandimage are essential strategies for Kopi Kenangan in Mustikajaya to build and maintain sustainable customerloyalty. Keywords: Service Quality, Brand Image, Customer Loyality, Kopi Kenangan, Mustikjaya